2015
DOI: 10.5812/ircmj.17(4)2015.27032
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cinnamon on Menstrual Bleeding and Systemic Symptoms With Primary Dysmenorrhea

Abstract: Background:Primary dysmenorrhea with interferes in daily activities can have adverse effects on quality of life of women.Objectives:Regarding the use of herbal medicine, the aim of this study was to assess the effect of cinnamon on primary dysmenorrhea in a sample of Iranian female college students from Ilam University of Medical Sciences (west of Iran) during 2013-2014.Patients and Methods:In a randomized double-blind trial, 76 female student received placebo (n = 38, capsules containing starch, three times a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
3
24
0
6
Order By: Relevance
“…Numerous studies have reported cinnamon as an aid for the ease of menstruation and in reducing the intensity of pain associated with menstrual cycle. [ 25 26 ] Hence, our findings are in congruence with reported literature. [ 27 ] The second most common use reported was in the regulation of blood sugar level.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have reported cinnamon as an aid for the ease of menstruation and in reducing the intensity of pain associated with menstrual cycle. [ 25 26 ] Hence, our findings are in congruence with reported literature. [ 27 ] The second most common use reported was in the regulation of blood sugar level.…”
Section: Discussionsupporting
confidence: 93%
“…Cinnamon is a widely known culinary herb and traditionally used in medicine applications. The effect of cinnamon has been studied during pregnancy [ 16 ], for diabetes control [ 17 ], and gynecological problems [ 18 ]. Its anti-inflammatory, cardioprotective, antioxidative, and antimicrobial properties have also been researched [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possibly useful methods: traditional Chinese herbal medicine, acupuncture and acupressure, moxibustion, omega-3 fatty acids, vitamin B1, vitamin E, magnesium, exercise, yoga, chaste tree, yarrow, toki-shakuyaku-san -Kampo medicine from Japan, cinnamon [81,[86][87][88][89][90][91][92][93][94][95]. Probably sound means: aroma oil massage (lavender oil, rose oil), and the inhalation of lavender scent or fragrance saffron treatment [96][97][98][99].…”
Section: Apitherapeutic Recommendations For the Treatment Of Primary mentioning
confidence: 99%